The association between COVID-19 preventive strategies, virtual reality exercise, use of fitness apps, physical, and psychological health: testing a structural equation moderation model - Menhas, Rashid; Qin, Luo; Saqib, Zulkaif Ahmed; Younas, Muhammad (Frontiers in Public Health, 2023)
Background: Directly or indirectly, individual psychosocial characteristics, motivation, and health consciousness factors help to maintain physical and psychological health through maintaining physical activity. Objective: In the current study, we investigated how fitness apps moderate the links among COVID-19 preventive strategies, virtual reality exercise, physical health, and psychological health in Chinese society. Method: A nationwide online survey across China was conducted under a snowball sampling design from February to June 2022. A total of 3,000 questionnaires were distributed across China via online platforms. A total of 2795 complete detailed replies were included in the final analysis. Structural equation modeling techniques were employed to analyze the collected data through Smart-PLS 3.0. Results: It has been statically proved that all the scales used in this inquiry to determine the mean scores, standard deviation, excess kurtosis, and skewness values were reliable and produced satisfactory results. The overall results (H1: β = 0.385, t = 15.699, p = 0.000; H2: β = 0.159, t = 7.405, p = 0.000; H3: β = 0.122, t = 5.435, p = 0.000; H4: β = 0.143, t = 6.493, p = 0.000; H5: β = 0.157, t = 6.444, p = 0.000; H6: β = 0.184, t = 9.071, p = 0.000; H7: β = 0.192, t = 9.319, p = 0.000; H8: β = 0.235, t = 11.899, p = 0.000; H9: β = -0.114, t = 4.872, p = 0.000; H10: β = 0.042, t = 2.872, p = 0.004; H11: β = 0.041, t = 2.699, p = 0.007) supported our hypothetical model and explained that using fitness apps and virtual reality exercise benefits physical and psychological health. Conclusion: The fitness app's primary purpose during and after the pandemic is to motivate users to keep up with their regular at-home workouts. Exercise and active living are helpful in the prevention of risk factors associated with physical inactivity.